COLLABORATION AND COMMUNICATION SKILLS OF ELEMENTARY SCHOOL STUDENTS’ IN INDONESIAN LANGUAGE LEARNING THROUGH RADEC - Hilma Mustika Fauziyyah; Prana Dwija Iswara; Wahyu Sopandi; Atep Sujana (Jurnal Cakrawala Pendas, 2024)
Collaboration and communication skills were essential as basic skills in the 21st century. This research described the forms of students’ collaboration skills in terms of the teamwork aspect, and the forms of students’ communication skills in terms of the verbal communication aspect, that emerge in Indonesian Language learning through RADEC. A qualitative approach with a case study type was applied in this study. The subjects were 3rd-grade students in one of the elementary schools in Bandung city. Data collection was carried out through observation, field notes, and interviews. Data was analyzed through data collection, data reduction, and conclusion. The results of this study show that 1) the form of student collaboration skills are through contributing to completing group assignments, help each other when having difficulties, appreciating the work of their friend in the group, and exchanging ideas and opinions, and 2) the form of student communication skills are being able to present the results of group discussions, being active argue and asking a question, using an appropriate language, respect each other’s opinions, brave and confident when speaking in front of the class. Collaboration in the discussion stage has yet to be visible; the reasons are that the students have yet to conclude the different opinions or answers even though the essence is the same, one person still dominates the discussion, and some students need to work on pre-learning questions. This research implied that Indonesian Language learning need to be designed to actively involved students to develop collaboration and communication skills by integrating innovative learning model such as RADEC.